Maternal and perinatal outcome in severe preeclampsia and eclampsia at the Rivers State university teaching hospital, Nigeria - Awoyesuku, Peter A.; John, Dickson H.; John, Dickson H.; Lebara, Lewis B.; Lebara, Lewis B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Severe preeclampsia and eclampsia remain a challenge in tropical obstetric practice. It is a major contributor to feto-maternal morbidity and mortality in developing countries. This study seeks to determine the prevalence, associated risk factors and the feto-maternal outcome of severe preeclampsia and eclampsia at the rivers state university teaching hospital (RSUTH). Method: A retrospective study of all women who had severe preeclampsia and eclampsia and were delivered at the RSUTH in a two-year period, 1ST January 2018 to 31ST December 2019, was carried out. Data on patients’ age, parity, education, booking status, gestational age at delivery, diagnosis, complications, mode of delivery and fetal sex, birth weight and Apgar scores were retrieved using structured pro-forma. Data were analyzed using SPSS version 20. Results: There were 4496 deliveries of which 128 had severe preeclampsia and eclampsia, giving a prevalence of 2.85%. Of these, 94 (73.4%) had severe preeclampsia and 34 (26.6%) had eclampsia. The mean age of the women ± SD was 29.84±5.44 years, median parity was para 1, and mean gestational age ± SD was 35.38±3.84 weeks. There were 10 maternal deaths giving case fatality of 7.8%. The mean birth weight ± SD was 2.61±0.91 kg and stillborn rate was 14.4%. There was significant association with maternal age, education, booking status, method of delivery and Apgar score of the baby. Conclusion: The prevalence in this study is high with associated high maternal mortality and stillborn rates. Timely and appropriate intervention including primary management and judicious termination of pregnancy will reduce mortality of mother and fetus.